Strategie uczenia się słownictwa specjalistycznego - Cholewa, Justyna (Neofilolog, 2024)
CLIL (Content Language Integrated Learning) is defined as the integration of specific content with language learning objectives. In higher education, it refers to the simultaneously teaching academic content and language skills in a given language. The core concept revolves around the use of a second/foreign language to acquire knowledge, while while concurrently enhancing language skills and vocabulary, including the acquisition of new specialist terms. Developing the lexical subsystem as a an integral component of linguistic competence is particularly important in the process of linguistic reception and production. Vocabulary learning strategies prove invaluable in this context. The discussion on the strategy of learning lexis in a foreign language appeared in the academic literature at the end of the last century. Previously, this matter was addressed in research on learning strategies and communication strategies. In academia, knowledge of professional vocabulary and terminology is indispensable for mastering specialist content taught in a second language. Learners must not only grasp the meaning of concepts, but also employ them with precision. So how do students learn new specialist vocabulary, and which lexis learning strategies do they use? This article aims to present the results of my own research on the application of specialized vocabulary learning strategies by students of economic sciences.